A „reunió” vitája a Reformáció 300. évfordulójának küszöbén - LUKÁCS, Olga (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2016)
The Dispute of the “Reunion” on the Threshold of the300ᵗʰ Anniversary of the Reformation. In the era of Enlightenment, independent thinking became highly significant for the modern man, who has built up a world-culture, which sought to be rid of the church tutelage. In the early 19th century, Protestant churches have responded differently to the strong secularization. They realized that society has changed and the old relations have been terminated. Consequently, many church-members did social work, helping the poor, creating nursing homes, etc. By contrast, the Roman Catholic Church refused all kinds of innovative changes and contact initiations. Thus, conservatism and restoration efforts came into view in the Catholic Church. In fact, the consolidation of the old Catholic tradition by new dogmas was attempted. Both on the Catholic and the Protestant side there were rationalists and romantics, whose enthusiasm for the union reached a point, where they considered that the reunification of not only the Protestants, but of all Christian denominations was possible. These and other such efforts, which aimed at “assimilation”, strengthened especially around the tercentenary of the Reformation. Such opinions came forth on both sides that the most worthy celebration of the rupture that had occurred three hundred years ago would be if the Protestants returned into “one flock”. The attempts at a union in the early 19th century have failed; therefore those who wished a union realized that there were insurmountable obstacles preventing it. These obstacles were primarily emotional and political conflicts, which were, in fact, the seeds of doctrinal and historical barriers.